Study on the Mechanism of Tooth Breakage Fault in Gear Rotor System Under Load Excitation - Haihan Zhang; Fang Ren; Jinhao Feng (Jixie chuandong)
The dynamics mechanism of the first-order gearbox and its connected two-span rotor system under load excitation and broken tooth fault is studied. Because of the time-varying meshing stiffness of gears and the unbalance of the rotor system， the coupling mathematical model of the gear rotor system is established based on the rotor dynamics and Lagrange equation， and the simulation model is established in Matlab/Simulink. The fault signals are simulated by numerical simulation， and different load excitation is simulated by signal generator. The dynamics response of the system caused by different load excitation and fault is analyzed by observing its time-frequency diagram. Finally， the time domain diagram of the measured signal is obtained and the frequency spectrum is analyzed through the experiment of gear tooth breaking under different load excitation. Then the rationality of the gear rotor system model is verified， which can provide an important theoretical basis for the fault diagnosis of the gear rotor system.